A co-produced mixed methods protocol: Exploring perceptions of oral health care and quality of life in people with mental health conditions - Michelle R. Zechner; Yuane Jia; Naja Hill; Ann Kasper; Jill York; Vaishali Singhal; Pamela Rothpletz-Puglia (PLoS ONE, 2025)
This planned mixed methods protocol is designed to explore oral health care for individuals living with serious mental health conditions (SMHC). It was co-produced by academics, people with lived experience of mental health conditions, and oral and mental health clinicians. The study seeks to explore oral health quality of life predictors and oral health care experiences of people diagnosed with serious mental health conditions (e.g. schizophrenia, bipolar disorder, major depression and general anxiety disorder) about their oral health care experiences. The research research will generate recommendations for creating positive oral healthcare experiences for people living with SMHC. Research co-production with people diagnosed with mental health conditions is a recommended strategy to improve the utility and relevance of health research, as well as empower a disenfranchised population.